Combination Therapy With Coenzyme Q10 and Trimetazidine in Patients With Acute Viral Myocarditis. Issue 2 (August 2016) - Shao, Liang; Ma, Aiqun; Figtree, Gemma; Zhang, Ping
Abstract : Background: Acute viral myocarditis is an inflammatory disease with global impact. Although it may resolve spontaneously, its course is not easily predicted, and there is a paucity of specific treatment options available with proven efficacy. Coenzyme Q10 (CQ10) and trimetazidine possess antioxidant and antiinflammatory effects. Methods: We examined the therapeutic efficacy of these agents in acute viral myocarditis both individually and in combination. Patients were blinded and randomized to receive CQ10 (n = 42), trimetazidine (n = 39), or CQ10 + trimetazidine (n = 43) treatment. Results: Serum inflammatory and oxidative stress marker and myocardial enzyme levels, and heart function were measured. Both CQ10 and trimetazidine decreased inflammatory and oxidative stress biomarker levels compared with baseline measurements. However, combination therapy with CQ10 and trimetazidine showed a significantly more powerful effect not only on markers of inflammation and oxidative stress, but also on left ventricular systolic function and troponin, compared with either treatment alone. Conclusion: This study confirmed the beneficial effect of CQ10 and trimetazidine individually, but demonstrated a superior effect of combining the therapies on cardiac left ventricular ejection fraction, and biochemical markers of myocardial damage in acute viral myocarditis.